Thoughts on industrialization, linkage and growth - United Nations (CEPAL Review, 1986)
This article discusses some issues which ought to be taken into consideration in the preparation of a new industrialization strategy that will make it possible to deal with internal disequilibria and face up to the predictable international situation in the coming years. The first section expounds the concept of linkage, which is regarded as the most significant of the attributes differentiating the productive and social structures of the advanced countries from those of the countries of the Latin American region. In the former, the characteristic feature is organic and interdependent growth of the various parts of the industrial complex, and in the latter, a transplantation of fragments of that structure which leaves in external hands complementary aspects of crucial importance for the functioning of the whole.